Enhancing Adolescent Well-being: The Impact of Comprehensive Sex Education on Knowledge, Consent, and Sexual Violence Prevention - Aroon Chai Khemkhaeng; Paitoon Narong Pravat; Thura Thiha; Thanda Hayma; Zeya Zeya (Intitute of Computer Science (IOCS), 2022)
This research delves into the critical topic of the influence of sex education on adolescents in the context of addressing sexual violence. The study aims to comprehensively examine the impact of sex education on adolescents' knowledge, attitudes, and behaviors related to sexual violence prevention. The research findings reveal several key insights. Effective sex education programs have a significant positive impact on adolescents' knowledge about sexual boundaries, resulting in a better understanding of consent and healthy relationships. Furthermore, these programs promote healthier attitudes toward consent, fostering a cultural context that supports safe and respectful interactions. Importantly, the study suggests that well-designed sex education has the potential to reduce the incidence of sexual violence among adolescents. The implications of this research are far-reaching. It underscores the importance of designing and implementing more effective sex education programs in schools and communities. By tailoring curricula to the specific needs of diverse adolescent populations and integrating evidence-based practices, educators and policymakers can equip young individuals with the knowledge and skills needed to navigate sexual relationships responsibly and safely. While this study provides valuable insights, it is essential to acknowledge its limitations, including sample size constraints and potential biases. Future research should consider longitudinal approaches to assess the long-term impact of sex education. In conclusion, this research serves as a crucial step toward developing strategies for preventing sexual violence among adolescents through comprehensive sex education. By disseminating these findings and fostering collaborative efforts among educators, policymakers, parents, and the broader community, we can work toward a safer and more informed future for our youth, free from the scourge of sexual violence